METODE PENSYARAHAN SUNAN AN-NASA’I PERBANDINGAN ANTARA IMAM Al-SUYUTI DAN AL-SINDI - HM. Suparta (Millah: Journal of Religious Studies, 2014)
Many great scholars have emerged and presented various kinds of monumental works in the field of hadith. Their work became popular which was then called kutub assitah and a book contains almost all hadith from Prophet Muhammad SAW. The books were the main guide for fuqaha’, mujtahid, and other writers. The writers, educators, psychologists, and sociologists obtained what they needed from the books. Sociological and political condition had influenced a conducive situation to work in the hadith. Nowadays, there is diversification of science that distinguish one science to another. It is not surprisingly if many branches of science have emerged, such as tafsir, hadith, fiqh, languages, literatures, and others. This article reviewed the commentary method of Imam Al-Suyuti and Imam Al-Sindi towards a hadith book, Sunan Al-Nasa’ial-Mujtaba by Imam Al-Nasa’i (d. 303 H.). This review was limited to critically observe the comparison of the commentary method by Imam Al-Suyuthi and Imam Al-Sindy. Brief biographies of Imam Al-Nasai, Imam Al-Suyuthi, and Imam Al-Sindy were also outlined. Commentary by Imam Al-Suyuti and Al-Sindi towards Sunan Al-Nasa’i facilitated the people to understand and review. Though, both of them wrote very short commentaries, the commentaries have brought advantages for Muslims, especially for those who get involved and care about the study of Prophet Muhammad SAW hadith. This condition was actually a main purpose of writing those two commentaries.